Tumor-derived exosomal miR-1247-3p induces cancer-associated fibroblast activation to foster lung metastasis of liver cancer - Fang, Tian; Lv, Hongwei; Lv, Guishuai; Li, Ting; Wang, Changzheng; Han, Qin; Yu, Lexing; Su, Bo; Guo, Linna; Huang, Shanna; Cao, Dan; Tang, Liang; et al. (Nature communications, 2018)
The communication between tumor-derived elements and stroma in the metastatic niche has a critical role in facilitating cancer metastasis. Yet, the mechanisms tumor cells use to control metastatic niche formation are not fully understood. Here we report that in the lung metastatic niche, high-metastatic hepatocellular carcinoma (HCC) cells exhibit a greater capacity to convert normal fibroblasts to cancer-associated fibroblasts (CAFs) than low-metastatic HCC cells. We show high-metastatic HCC cells secrete exosomal miR-1247-3p that directly targets B4GALT3, leading to activation of β1-integrin–NF-κB signaling in fibroblasts. Activated CAFs further promote cancer progression by secreting pro-inflammatory cytokines, including IL-6 and IL-8. Clinical data show high serum exosomal miR-1247-3p levels correlate with lung metastasis in HCC patients. These results demonstrate intercellular crosstalk between tumor cells and fibroblasts is mediated by tumor-derived exosomes that control lung metastasis of HCC, providing potential targets for prevention and treatment of cancer metastasis. How tumor cells control metastatic niche formation is not fully understood. Here, the authors show in a lung metastatic niche, high-metastatic hepatocellular carcinoma cells secrete exosomal miR-1247-3p that leads to activation of β1-integrin-NF-κBsignalling, converting fibroblasts to cancer-associated fibroblasts.